Արիացիները Պախխուվայում - Քոսյան, Արամ («Զանգակ - 97»)
In one of the previous articles the aulhor had pointed on the existence of two "Aryan" personal names in the cuneiform Hittite text of the XIVc. B.C. dealing with the country of Isuwa (Uiiarna and Uwa-[...]) and one Hurrian (Kumarpi). Further studies had revealed two more names bom by the eiders of the neighboring Pahhuwa - Arziutta and Lupakiutta. Both names are built with the well-known Old Ind. suffix -ut(i)a. As to the stem of these names. Am- could be compared with the Urartian (of Old Armenian origin) arsibi, the another - with the IE *ulp-, *lup- "wolf, dog, chakal".
Keywords: Պատմություն